Ion association and solvation behavior of nicotinium dichromate in water-N,N-dimethyl formamide mixtures by a conductometric study - Radhika, Veerati; Srinivas, Nalamasa; Manikyamba, Prerepa (European Journal of Chemistry, 2012)
The electrical conductance of nicoitinium dichromate has been measured in water-N,N-dimethyl formamide mixtures of different compositions in the temperature range 283-313 K. The limiting molar conductance, Lo and the association constant of the ion-pair, KA have been calculated using Shedlovsky equation. The effective ionic radii (ri) of (C6H6O2)+ and (C6H6O2NCr2O7)- ions have been determined from Lio values using Gill’s modification of the Stokes law. The influence of the mixed solvent composition on the solvation of ions has been discussed with the help of ‘R’-factor. Thermodynamic parameters are evaluated and reported. The results of the study have been interpreted in terms of ion-solvent interactions and solvent properties.